Mathematical Modeling and Simulation of Anaerobic Digestion of Solid Waste. (2016) - Manjusha, C.; Beevi, B. Sajeena
Abstract: Waste management and energy crisis are the greatest issues that the world is facing today. This problem can be overcome by anaerobic digestion of solid waste, where the waste is converted to biogas: a mixture of mainly carbon dioxide and methane gas. Because of the growing need of anaerobic digestion of solid waste, increased efforts in reducing biogas plant design cost and optimizing process operation is crucial. One way of doing this can be through mathematical modeling of the anaerobic process. The purpose of this paper is to use the Anaerobic Digestion Model no.1 (ADM1), which gives complete information about the physico-chemical reactions in the anaerobic process, to investigate how different parameters in the model affect biogas production. A model was implemented in MATLAB and can be used to find out how the factors such as pH and Volatile Fatty Acid (VFA) affect the daily biogas production.